INFORMATION MODELING OF CONSTRUCTION OBJECTS: FEATURES OF APPLICATION AND DEVELOPMENT - T. Yu. Shemyakina (Вестник университета)
The concept of database creation (modeling) of a building object (Building Information Model further – BIM) – an approach to erection, equipment, support, operation and repair of a building, which includes collection and complex processing during the design process of architectural, technological, economic and other information about the building under construction has been considered. The main advantages of BIM in construction have been highlighted. Advantages and practice of application of informational modeling of construction objects have been studied. Proposals to solve the problems that determine the further effective expansion of the practice of using information modeling of construction facilities have been formulated. In particular, these are modernization of existing and development of domestic software; transition to BIM technologies to public-private partnership facilities; consideration of the BIM model as the main data source for the partner relationship management system, expertise in architectural and urban planning decisions and the project declaration; development and application of intermediate (transitional) period procedure for application of BIM technologies - stages of assessment of readiness of participants of investment and construction complex for application of BIM technologies, application of mechanism of interaction between participants of investment and construction complex and active creation of new digital system of construction facility management.